PELATIHAN KECERDASAN BUATAN UNTUK PENGEMBANGAN MEDIA PEMBELAJARAN BAGI GURU SMA DI PROVINSI LAMPUNG - Rahman Taufik; Rico Andrian; Muhammad Ikhsan; Dea Delvinata Riyan (FMIPA Unila, 2026)
The digital era demands that Senior High School teachers adopt new technologies to create interactive and effective learning media, yet the implementation of AI tools in schools remains low. This community service activity aims to enhance the competency of Senior High School teachers in developing learning media through training that utilizes AI tools, such as Canva AI and Gamma AI. The implementation method utilized a blended learning approach over one week (September 21–26), combining face-to-face sessions at the University of Lampung with self-paced learning supported by a Learning Management System. A total of 30 participants registered for the program, with 11 teachers completing the entire series of training activities. The comprehensive training module covered AI fundamentals, practical use of Generative AI, and the implementation of AI in material development and assessment. The evaluation results showed a significant increase in competency, with the average pretest score rising from 77.5 to 89 on the posttest. This improvement yielded an N−Gain value of 0.51 (medium category), confirming the program's effectiveness in transferring practical knowledge and skills. Thus, the training successfully equipped SMA teachers with the ability to leverage AI for efficiency and innovation, which is expected to enhance the quality of learning at partner schools.